Brand Resonance Behavior among Online Brand Community - Shaari, Hasnizam; Ahmad, Intan Shafinaz (International Review of Management and Marketing, 2017)
Brand commitment studies had gained considerable attention in today's marketing practices. Sustaining the brand competitive advantages become challenging especially in the context of digital marketing. Development of Web 2.0 that enables interactive communication had offered a new mechanism for owner of the brand to strengthen the bond among their admirers and users via online brand community. Attitude and behavior of online brand community members can be crucial to overall brand competitive advantage. This is because brand image and reputation can be praised or tarnished just by one click from the members. Hence, owner of the brand should understand how online brand community commitment could affect overall brand performance. This study attempts to examine how brand trust and brand community commitment among online brand community will affect their brand resonance behavior namely brand referral and intention to purchase new product of the brand in the future. The study among 167 members of online brand community indicate that brand trust and brand community commitment play a significant roles in determining brand community behavior such as brand referral and intention to purchase new product. Discussion and recommendation for future research direction also were discussed in this article. Keywords: Online Brand Community, Brand Resonance Behavior, Brand Loyalty JEL Classifications: M31, M37